17. Effects of Cariprazine on Negative Symptoms, Cognitive Impairment, and Prosocial Functioning in Patients With Predominant Negative Symptoms: Post Hoc Analysis of a Phase III, Placebo-, and Active-Controlled Study. (20th March 2017) - Daniel, David; Nasrallah, Henry; Earley, Willie; Durgam, Suresh; Lu, Kaifeng; Szatmári, Balázs; Laszlovszky, István; Németh, György; Patel, Mehul
Abstract: Background: Negative symptoms and cognitive deficits are core symptoms of schizophrenia that have proven to be difficult to treat and are associated with poor social/vocational functioning. Cariprazine (CAR), a D3/D2 receptor partial agonist, is approved in the United States for the treatment of schizophrenia in adults. This post hoc analysis of a Phase 3, randomized, double-blind, placebo- and active-controlled CAR study in adults with acute exacerbation of schizophrenia evaluated the effects of CAR on positive, negative, cognitive, and prosocial functioning domains in a subset of patients with predominant negative symptoms (PNS). Methods: Randomized patients received 6 weeks of double-blind treatment with CAR 3 mg/d, CAR 6 mg/d, aripiprazole 10 mg/d (ARI), or placebo (PBO). For post hoc analyses, patients with PNS were identified using baseline Positive and Negative Syndrome Scale factor scores (PANSS-FS) for positive symptoms (score ≤19; mild to moderate), negative symptoms (score ≥24; moderate to severe), and cognitive impairment (score ≥27; severe). Efficacy parameters included change from baseline to Week 6 in PANSS total score and PANSS-FS for negative, cognitive, and prosocial domains. Results: In all, 131 of 604 randomized patients met criteria for PNS (placebo = 35; CAR 3 mg/d = 27; CAR 6 mg/d = 34; ARI = 35). For CAR 6 mg/d, least squares mean differences (LSMDs) of change from baseline to Week 6 versus placebo were statistically significant on the PANSS total score (-13.9, P  = .0132), and negative (-3.3, P  = .0112), cognitive (-1.6, P  = .0092), and prosocial (-2.9, P  = .0035) factor scores. For CAR 3 mg/d, LSMDs versus placebo at Week 6 were statistically significant on the PANSS total score (-14.0; P  = .0156), and cognitive (-1.5, P  = .0164) and prosocial (-2.5, P  = .0187) factor scores. For the negative symptoms factor score, numerical improvement was seen for CAR 3 mg/d over placebo, but the LSMD was not statistically significant at Week 6 (-2.6, P  = .0515). In contrast, LSMDs for aripiprazole versus placebo were not statistically significant on PANSS total score (-9.6, P  = .0800), negative (-0.6, P  = .6449), cognitive (-0.6, P  = .3108), or prosocial factor scores (-1.1, P  = .2482). In addition, on PANSS-FS for negative symptoms, the LSMD between CAR 6 mg/d and ARI met statistical significance (-2.8, P  = .0315). Conclusion: Cariprazine significantly improved overall schizophrenia symptoms, as well as negative, cognitive, and prosocial function versus placebo, in a subset of patients with PNS. These results suggest that cariprazine may be an effective treatment option for the negative symptoms of schizophrenia and its associated domains. Limitations of this analysis include the short duration (6 weeks) for evaluation of negative symptom improvement and the potential that improvements in at least some of the negative symptoms may have been secondary to improvements in positive symptoms.